Usefulness of extracorporeal membrane oxygenation in status asthmaticus with severe tracheal stenosis - Odigwe, Chibuzo (Proc (Bayl Univ Med Cent), 2020)
Extracorporeal membrane oxygenation, traditionally used to treat refractory hypoxemic respiratory failure due to acute respiratory distress syndrome, is being used to treat other etiologies of severe respiratory failure refractory to conventional mechanical ventilation. We present a 30-year-old woman with concomitant life-threatening airway obstruction due to severe tracheal stenosis and status asthmaticus treated effectively with veno-venous extracorporeal membrane oxygenation.